Emerging Streptococcus pneumoniae Strains Colonizing the Nasopharynx in Children After 13-valent Pneumococcal Conjugate Vaccination in Comparison to the 7-valent Era, 2006–2015. Issue 8 (August 2016) - Kaur, Ravinder; Casey, Janet R.; Pichichero, Michael E.
Abstract : Background: After introduction of the 7-valent pneumococcal conjugate vaccine (PCV7) in the United States in 2000, emergence of replacement serotypes occurred, leading to the introduction of a 13-valent pneumococcal conjugate vaccine (PCV13) in 2010 that contained all PCV7 serotypes plus 6 additional serotypes (1, 3, 5, 6A, 7F and 19A). Here, we describe a 9-year prospective, longitudinal study characterizing Streptococcus pneumoniae strains colonizing the nasopharynx (NP) of young children based on serotype, sequence type (ST) and antibiotic susceptibility during the PCV7 and PCV13 eras. Methods: NP samples were obtained for pneumococcal identification from prospectively followed children at 6, 9, 12, 15, 18, 24 and 30 months of age. A total of 1072 visits during the PCV7 era (June 2006 to September 2010) and 2044 visits during the PCV13 era (October 2010 to September 2015) were included from 665 children. Serotyping and multilocus sequence typing types of Streptococcus pneumoniae isolates were evaluated along with their antibiotic resistance pattern. Results: A total of 1045 Streptococcus pneumoniae were isolated; 350 during the PCV7 era and 685 during the PCV13 era. The most common serotypes identified during the PCV7 era were 19A and 23B compared with 35B, 23B and 21 in PCV13 era. Serotypes 15A/B/C emerged in equal proportion during the PCV13 era. Serotypes 16 and 20 were only observed in the PCV13 era. NP carriage of 19A persisted 5 years after PCV13 introduction (5% of all isolates). Multilocus ST 199 remained a dominant ST during both the PCV7 and PCV13 eras, and ST558 and ST62 emerged after PCV13. Antibiotic resistance to penicillin, ceftriaxone, cefotaxime, erythromycin, tetracycline and trimethoprim/sulfamethoxazole significantly decreased from the PCV7 to the PCV13 era. Conclusions: Serotypes 35B, 23B, 21 and 15A/B/C rapidly emerged as NP colonizers in the early PCV13 era. Genetically divergent strains with ST558 and ST62 emerged. Resistance to common antibiotics declined after the introduction of PCV13.